Acidified seawater impacts sea urchin larvae pH regulatory systems relevant for calcification - Stumpp, Meike (National Academy of Sciences, 2012)
Calcifying echinoid larvae respond to changes in seawater carbonate chemistry with reduced growth and developmental delay. To date, no information exists on how ocean acidification acts on pH homeostasis in echinoderm larvae. Understanding acid–base regulatory capacities is important because intracellular formation and maintenance of the calcium carbonate skeleton is dependent on pH homeostasis. Using H(+)-selective microelectrodes and the pH-sensitive fluorescent dye BCECF, we conducted in vivo measurements of extracellular and intracellular pH (pH(e) and pH(i)) in echinoderm larvae. We exposed pluteus larvae to a range of seawater CO(2) conditions and demonstrated that the extracellular compartment surrounding the calcifying primary mesenchyme cells (PMCs) conforms to the surrounding seawater with respect to pH during exposure to elevated seawater pCO(2). Using FITC dextran conjugates, we demonstrate that sea urchin larvae have a leaky integument. PMCs and spicules are therefore directly exposed to strong changes in pH(e) whenever seawater pH changes. However, measurements of pH(i) demonstrated that PMCs are able to fully compensate an induced intracellular acidosis. This was highly dependent on Na(+) and HCO(3)(−), suggesting a bicarbonate buffer mechanism involving secondary active Na(+)-dependent membrane transport proteins. We suggest that, under ocean acidification, maintained pH(i) enables calcification to proceed despite decreased pH(e). However, this probably causes enhanced costs. Increased costs for calcification or cellular homeostasis can be one of the main factors leading to modifications in energy partitioning, which then impacts growth and, ultimately, results in increased mortality of echinoid larvae during the pelagic life stage.